Vibration control based metamaterials and origami structures: A state-of-the-art review. (December 2021) - Ji, J.C.; Luo, Quantian; Ye, Kan
Highlights: Metamaterials, origami structures, and their applications to vibration control are discussed. Metamaterials with abnormal features are reviewed based on the unusual values of elastic constants. Auxetic, band gap and pentamode metamaterials are reviewed for vibration and sound control . Origami structures are discussed on their capacities for vibration control. Future research directions are given for this emerging interdisciplinary research field. Abstract: Vibration and sound control is critical to many practical engineering systems in order to minimise the detrimental effects caused by unavoidable vibrations and noises. Metamaterials and origami-based structures, which have attracted increasing interests in interdisciplinary research fields, possess many peculiar physical properties, including negative Poisson's ratios, bi- or multi-stable states, nonlinear and tuneable stiffness features, and thus offer promising applications for vibration and sound control. This paper presents a review of metamaterials and origami-based structures as well as their applications to vibration and sound control. Metamaterials are artificially engineered materials having extremal properties which are not found in conventional materials. Metamaterials with abnormal features are firstly discussed on the basis of the unusual values of their elastic constants. Recent advances of auxetic, band gap and pentamode metamaterials are reviewed together with their applications to vibration and sound mitigations. Origami, as the ancient Japanese art of paper folding, has emerged as a new design paradigm for different applications. Origami-based structures can be adopted for vibration isolation by using their multi-stable states and desirable stiffness characteristics. Different origami patterns are reviewed to show their configurations and base structures. Special features, such as bi- or multi-stable states, dynamic Poisson's ratios, and nonlinear force–displacement relationships are discussed for their applications for vibration control. Finally, possible future research directions are elaborated for this emerging and promising interdisciplinary research field.